Bio-inspired snake robot locomotion: a CPG-based control approach - Billah, Md. Masum; Khan, Md. Raisuddin (2015)
Biological creatures perform their motion by using distributed spinal control system. Natural control generates motion instantly based on the feelings from the environment. In line with this concept, an artificial control system is known as Central Pattern Generator (GPG) is an online motion generation system that can be generated instantly like spine based control system. CPG also generates online motion instantly. Past control systems were used the predetermined trajectory information to control snake robot. CPG system makes a solution to overcome such kind of predetermined data. Snake robots are generally consists of serially connected multiple links. A rhythmic function is used to model the bending of each link of the snake robot. CPG generates the recurring signal from the input signal by using its internal biological oscillators. Performance of CPG control system is established from the obtained simulation result and planned in snake robot application. This research shows a novel algorithm to generate online sinusoidal motion generation using CPG for planar space. To optimize the CPG parameters, for the optimum output signals, particle swarm optimization (PSO) is applied in this paper. The performances of the proposed method are verified by simulation results.